The role of cooperative learning with team assisted individualization to improve the students’ self proficiency - Georgina Maria Tinungki (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2017)
The importance of learning mathematics can not be separated from its role in all aspects of life. This research aims to analyze the achievement of the students’ self-proficiency who are taught by using cooperative learning with Team Assisted Individualization (TAI) and conventional learning. Students need to possess self-proficiency ability well so that they could have confidence that they are capable of confronting and of solving their daily life problems in general or mathematical tasks in particular. The population in this research was students of Statistics study program at one of public universities in Makassar. The sampling technique used in this research was purposive sampling, while the instrument used was self-proficiency scale (SPr) which has been validated. The data were analyzed by using parametric and non-parametric statistics. The result of this research is that the achievement of the students’ self-proficiency who are taught by using cooperative learning with TAI is better than students who are taught by using conventional learning.